Meta Analisis: Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis - Bettri Yustinaningrum (LPPM Universitas Advent Indonesia, 2021)
To be able to improve students' problem solving abilities, one way is to choose the right mathematics learning model. One of the learning models that can be used is the problem based learning model. The purpose of this study was to re-analyze the effect of the problem-based learning model on students' mathematical problem solving abilities by reviewing, summarizing data and analyzing some of the research results that have been published on Google Scholar as many as 14 articles by means of statistics. The type of research in this article is a type of meta-analysis research. The research steps included data collection, coding, calculating the increase in problem-solving abilities and the effect size, identifying whether there were differences in the average, and drawing conclusions. Based on the results of the study, the average effect size was 2.02 with a very large category. Meanwhile, based on the paired sample t-test, the value of sig (2 tailed) = 0.000 <α = 0.05, which means that there is a difference in the average problem-solving ability before and after being treated with the problem based learning model. Based on the average effect size and paired sample t-test results, it can be concluded that the problem-based learning model has an effect on students' mathematical problem solving abilities.